Study on the Effect of Consumption of Sugar-Sweetened Beverages on Psychosocial Behavior of Children in Saudi Arabia - Bano, Rafia; Noor, Tasneem; Fatima, Waseem; Hamayun, Rahma; Bahathig, Abeer; Trabelsi, Saoussen; Aljarad, Sarah Jarad (International Journal of Child Health and Nutrition, 2025)
Background and objectives: The goal of the study was to see how sugar-enhanced beverages affected children’s psychosocial behavior. Expansions in the use of sugar-enhanced drinks (SSB) during youth have mirrored global patterns in the epidemic of experience growing up stoutness. Furthermore, the study aims to determine the rates at which Saudi children use SSBs and their relationship to mental effects, as well as the mental aspects that are most affected by SSB use. Methodology: For this research, 400 guardians from Saudi Arabia were selected as samples, and the probability purposive sampling technique was used to collect samples. Questionnaires were designed and validated through the pilot survey. Three categories were made in the questionnaires to assess the sociodemographic characteristics, consumption patterns of sugar-sweetened beverages, and behavioral problems. Chi-square, t-test, and logistic regression were used to analyze the data statistically using SPSS 23 software. Results: Results and outcomes of the research demonstrated that mental health issues and physical as well as psychosocial problems were the main effects of excessive use of sugar-sweetened beverages Causes. Restlessness, lack of concentration, loss of temper, lack of confidence, and feelings of sickness were found to be the most experienced symptoms. Conclusion: The intake of sugar-sweetened beverages negatively impacts children’s physical and mental health. It impacts increased heart issues, obesity, diabetes, and aggressive behavior. Limitations: This is a cross-sectional study, and the causal relationship is unclear.